If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + 2xy + -12 = -30 Reorder the terms: -12 + 2xy + 15y = -30 Solving -12 + 2xy + 15y = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 2xy + 12 + 15y = -30 + 12 Reorder the terms: -12 + 12 + 2xy + 15y = -30 + 12 Combine like terms: -12 + 12 = 0 0 + 2xy + 15y = -30 + 12 2xy + 15y = -30 + 12 Combine like terms: -30 + 12 = -18 2xy + 15y = -18 Add '-15y' to each side of the equation. 2xy + 15y + -15y = -18 + -15y Combine like terms: 15y + -15y = 0 2xy + 0 = -18 + -15y 2xy = -18 + -15y Divide each side by '2y'. x = -9y-1 + -7.5 Simplifying x = -9y-1 + -7.5 Reorder the terms: x = -7.5 + -9y-1
| 7u+5v= | | 2(3x+5)=-50+54 | | 3[2-(3j-6)]+4[6]-(1-2j)=4-5j | | 9(8)+4y=36 | | 2x^2-10x=-2 | | -7(w+8)=-3w-20 | | 7x-21=-7x-35 | | 0.4x-0.3x+8=9 | | 5x-29=9(x-1) | | 2t+3=4t-l | | 3x^3-2x^2+64=0 | | x^2-9x=-162 | | -18p-5(5-5p)=4(p-2)-17 | | 0.09x^2+5x+5=0 | | 6(x+6)=8x+38 | | 2x-(-10)=6 | | 3z-8-z=0 | | 3x^2-8x=-3 | | 72=-x+177 | | 3x^2-3x=8 | | -8x=-4x^2+12 | | 59=166-y | | y=-7(7)+8 | | -9x=-2x^2+18 | | X-1=-2x+5 | | (4x-6+5x)+(9-5x+3-2x)=7x-(1-6x) | | 4x^2+9x=1 | | y=21-0.25x | | 39=3(4)+27 | | x+3=2x+14 | | 6x-y+18=0 | | 4x+7-6x=13 |